Soft Soldering of Steel DIN CK50 Using ASTM 50A and ASTM 63A - Abdalrahman, Rzgar Mohammed (Sulaimani Journal for Pure and Applied Sciences, 2010)
The research presents some experimental data concerning the relation between the shearing strength of soldered joints and holding time. Two types of solders ASTM 50A (Sn50Pb50) and ASTM 63A (Sn63Pb37) were used to joint medium carbon steel type DIN CK50 of 3 mm thickness. Lap joint design was employed. Muffle furnace used for heating with holding (reflow or dwell) times of 10, 20, 30, 35, 40, 45 and 50min. Maximum shear strength was obtained when the eutectic solder (ASTM 63A) used with 35 min. as holding time. Clear intermetallic compounds were shown at the interface, whereas the X-ray detected the formation of many phases like FeSn and FeSn2.
Keywords: soldered joints; solders; shear tests; intermetallic compounds